2020
DOI: 10.3390/w12041165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Scientific Scrutiny after the 2016 Braunsbach Flash Flood on Flood-Risk Management in the State of Baden-Württemberg, Germany

Abstract: This paper presents interdisciplinary research focusing on the municipality of Braunsbach in the German state of Baden-Württemberg, where, in May 2016, a flash flood attracted media attention and scientific scrutiny that highlighted the fact that certain aspects of flood risk were overlooked during earlier assessments conducted by the municipality, such as sediment transport. Using a network analysis and a focus-group discussion, we traced the flow of knowledge through the reported interactions between governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In mountainous regions such as the state of BW, this is aggravated by the risks of erosion, bedload, and driftwood, which can lead to higher damage. BW has already established a well‐integrated flood risk governance arrangement that accounts for bottom‐up coordination with municipalities in cross‐municipal partnerships—so‐called flood partnerships—that also include the participation of additional stakeholders and interested citizens (Newig et al, 2014; Witting, Brandenstein, Zarfl, & Lucía, 2020). Flood partnerships have existed since the 1990s in response to major floods in the area, long before the implementation of the EU Floods Directive of 2007.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mountainous regions such as the state of BW, this is aggravated by the risks of erosion, bedload, and driftwood, which can lead to higher damage. BW has already established a well‐integrated flood risk governance arrangement that accounts for bottom‐up coordination with municipalities in cross‐municipal partnerships—so‐called flood partnerships—that also include the participation of additional stakeholders and interested citizens (Newig et al, 2014; Witting, Brandenstein, Zarfl, & Lucía, 2020). Flood partnerships have existed since the 1990s in response to major floods in the area, long before the implementation of the EU Floods Directive of 2007.…”
Section: Resultsmentioning
confidence: 99%
“…Initiated by the observed broker and under the direction of the Executive Board of the city of Stuttgart (Ref. 53.2), a specialist group was founded after a severe flash flood in order to foment collaboration between colleagues at the state level, local decision makers and experts, to determine the dangers of heavy rain and bedload for municipalities (Witting, Brandenstein, Zarfl, & Lucía, 2020). The group's goal is to use this event as a template to improve flood risk mapping.…”
Section: Case II Governing Flash Flood Hazards In Bwmentioning
confidence: 99%
“…The contributions by Witting et al [36], Breuer and Oswald Spring [38], and to some extent also the contribution by Arfan et al [44] show how issues are placed on discussion or decision agendas. One possibility is through the occurrence of a natural disaster, as was the case with the flood in Braunsbach [36].…”
Section: Discussionmentioning
confidence: 99%
“…In May 2016, a severe flash flood in the municipality of Braunsbach in the German State of Baden-Württemberg attracted media attention and was on the political agenda because of the extensive damage caused by the disaster. Using a network analysis and a focus-group discussion, Witting et al [36] investigate the flow of knowledge through the reported interactions between governmental, private, and academic actors in the period following the event. The authors reveal that the extreme event motivated scientists to assess the hazard, who then highlighted that certain aspects of flood risk were overlooked during earlier assessments conducted by the municipality, such as sediment transport.…”
Section: When Do Water Issues Receive Attention? When Does the Attent...mentioning
confidence: 99%
“…We evaluate our proposed method on two real-world hourly raingauge datasets from different regions: Hong Kong (HK) in China and Baden-Württemberg (BW) in Germany. Due to the great variability of terrain, these two regions often suffer from regional rainfall-induced natural disasters, e.g., landslides [8] in Hong Kong and flash floods [30] in BW.…”
Section: Experiments Setupmentioning
confidence: 99%